THE MASS MEDIA FREEDOM IN A STATE OF EMERGENCY: INFODEMIC VS. COVID-19 PANDEMIC - Aneta Stojanovska-Stefanova; Hristina Runcheva Tasev (Sciendo, De Gryter, 2020)
Information, as well as freedom of expression and freedom of the media are essential for democratic society and fundamental characteristic of modern states. The year 2020 will be remembered as a year of pandemic caused from Covid-19 (coronavirus) and a year of response to unexpected challenge that the spread of the virus caused. In the times of pandemic and any type of crisis, the media always plays a key role in informing the public all over the Globe. This paper aims to make theoretical descriptive research and analysis of the influence of coronavirus on news consumption, the role of media in communication and presentation of important developments during pandemic. The authors present an overview of the media system and the latest developments in the EU in preventing fake news related to the pandemic. We conclude that media plays key role in informing the citizens during pandemic and therefore they have increased responsibility in providing reliable information. At the same time, since the beginning of the Covid-19 pandemic, the media have been challenged with parallel outbreaks of disinformation and misinformation about the virus, ranging from fake coronavirus cures, false claims and harmful health advice to wild conspiracy theories. Disinformation can in turn speed up the spread of disease, hinder effective public health responses, as well as create confusion, fear and distrust. We highlight the fundamental function of creating awareness regarding the topic based on facts, and the need of media for preventing panic and fostering people’s understanding by ‘checking the source and information twice’.
Keywords: media system, pluralism, rumors, fake news.